A transferência da família real portuguesa para o Brasil: explicação histórica em estudantes brasileiros e portugueses - Alves, Ronaldo Cardoso [UNESP] (Universidade Estadual de Londrina, 2013)
Based on the relationship between the concept of Historical Consciousness, as Jörn Rüsen and Reinhart Koselleck proposed, and the concept of Historical Explanation, proposed by Isabel Barca, the article presents an analytical course that allows you to check levels of explanation in historical narratives produced by students Brazilian and Portuguese from the interpretation of sources related to a historical fact: the transfer of the Portuguese royal family to Brazil (1808).

Baseado na relação entre a concepção de Consciência Histórica, tal como Jörn Rüsen e Reinhart Koselleck propõem, e o conceito de Explicação Histórica, proposto por Isabel Barca, o artigo apresenta um percurso analítico que permite verificar níveis de explicação histórica em narrativas elaboradas por estudantes brasileiros e portugueses a partir da interpretação de fontes relacionadas a um fato histórico: a transferência da família real portuguesa para o Brasil (1808).
Keywords: Historical consciousness; Historical explanation; Meta-historical concepts; Didactic of history; History education; Consciência histórica; Explicação histórica; Conceitos meta-históricos; Didática da história; Educação histórica